GRÁFICO TÁTIL: uma proposta inclusiva para abordar gráficos e ajuste de curvas no ensino de Física. - SILVA, Gladiston Xavier Diniz (2019)
The teaching and learning process in the perspective of inclusive education is one of the most relevant issues for current teaching. Therefore, educational institutions need to be organized properly in order to comply with the current Federal Legislation, which guarantees people with disabilities access to regular schools. Thus, this study focuses on teaching Physics from an inclusive perspective for visually impaired students. In this study, with a bibliographical, qualitative and applied character, a methodology is developed that transposes the visual information of a graphic into tactile information, necessary for people with a visual impairment to understand it. The linearization method was applied so the student can adjust experimental data, elaborating empirical models of physical phenomena. The methodology developed was applied on third grade students of Ensino Médio (equivalent to High School) at a public school in the city of São Luís/MA. Results show that the adapted material, besides providing visually impaired students with reading, interpretation and creation of their own graphics, was widely approved by all – those who can see and those who cannot see.